2011
DOI: 10.1186/bcr3017
|View full text |Cite
|
Sign up to set email alerts
|

A new gene expression signature, the ClinicoMolecular Triad Classification, may improve prediction and prognostication of breast cancer at the time of diagnosis

Abstract: IntroductionWhen making treatment decisions, oncologists often stratify breast cancer (BC) into a low-risk group (low-grade estrogen receptor-positive (ER+)), an intermediate-risk group (high-grade ER+) and a high-risk group that includes Her2+ and triple-negative (TN) tumors (ER-/PR-/Her2-). None of the currently available gene signatures correlates to this clinical classification. In this study, we aimed to develop a test that is practical for oncologists and offers both molecular characterization of BC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…As in our previous study [4], this study showed that CMTC-1 was again correlated with low tumor grade, and CMTC-2 and CMTC-3 were associated with high grade in both the second internal cohort (Figure 2A) and the new external validation cohort (Table 1). Patient’s age, tumor size and lymph node status were not associated with CMTC in the internal validation cohort of the 284 breast cancers, but these variables became statistically significant in the new larger external validation cohort of 2,181 breast cancers: more younger patients were found in CMTC-3 than in CMTC1-1 and CMTC-2; more patients with a larger tumor size or lymph node positive disease were found in CMTC-2 and CMTC-3 than in CMTC-1 (Table 1).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…As in our previous study [4], this study showed that CMTC-1 was again correlated with low tumor grade, and CMTC-2 and CMTC-3 were associated with high grade in both the second internal cohort (Figure 2A) and the new external validation cohort (Table 1). Patient’s age, tumor size and lymph node status were not associated with CMTC in the internal validation cohort of the 284 breast cancers, but these variables became statistically significant in the new larger external validation cohort of 2,181 breast cancers: more younger patients were found in CMTC-3 than in CMTC1-1 and CMTC-2; more patients with a larger tumor size or lymph node positive disease were found in CMTC-2 and CMTC-3 than in CMTC-1 (Table 1).…”
Section: Resultssupporting
confidence: 83%
“…The ability of CMTC to predict prognosis of breast cancers was strongly supported by the analyses on the first external validation cohort reported previously [4]. This cohort consisted of 2,239 breast cancers collected from 13 breast cancer datasets using Affymetrix and Agilent microarray platforms, and had a median follow-up of 6.33 years.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Most patients are treated similarly using an empiric gemcitabine-based approach, despite the fact that pancreatic adenocarcinoma is a heterogeneous disease with significant molecular differences between tumors [3]. In the modern era of molecular profiling, there has been a push to identify molecular signatures that could be used to predict tumor biology, and perhaps tailor treatment [4-8]. …”
Section: Introductionmentioning
confidence: 99%